The effects of Jebisa on nutrient intake and hematology profile in adolescent girls with anemia - MARTHA ARUM NUGRAHENI; DONO INDARTO; ETI PONCORINI PAMUNGKASARI; TRI NUGRAHA SUSILAWATI; SINU ANDHI JUSUP; Niniek Purwaningtyas; SETYO SRI RAHARDJO; SRI WULANDARI; KEZIA ELIAN DEVINA (Smujo International, 2024)
Abstract. Nugraheni MA, Indarto D, Pamungkasari EP, Susilawati TN, Jusup SA, Purwaningtyas N, Rahardjo SS, Wulandari S, Devina KE. 2024. The effects of Jebisa on nutrient intake and hematology profile in adolescent girls with anemia. Nusantara Bioscience 16: 210-218. Anemia is a public health problem that often occurs in adolescent girls in developing countries, including Indonesia, mainly due to iron deficiency. Iron supplementation has been implemented for anemia treatment, but there are some side effects for long-term use. The Indonesian Government also fortified wheat flour with iron and folic acid, but the efficacy of fortification remains unclear. Snake fruit seeds contain high iron (Fe) and vitamin C levels but they are usually thrown away. Therefore, this study aimed to analyze the effects of jelly-containing snake fruit seed flour (SSF) and sugar, now called Jebisa, on macro and micronutrient intake and hematological profile in adolescent girls with anemia. Thirty tree adolescent girls from five public high schools in Sukoharjo Regency, Central Java, Indonesia, were randomly grouped into three categories: Control group (C) was given plain jelly with Fe tablets, and Treatment groups (T1-T2) were given jelly-containing 18.52 g and 37.04 g SSF, respectively, for 60 days. Data were analyzed using the one-way and repeated measures ANOVA tests followed by the Post Hoc Tukey and the Kruskal-Wallis test for non-parametric data. A significant value was set to p<0.05. The results suggested that the average daily energy intake, carbohydrates, and fibers significantly increased in the T1 and T2 groups compared to the C group (p<0.05). The average Fe intake in the T2 (19.59±1.70 mg/day) was significantly higher than that of T1 (10.74±2.40 mg/day) and C group (4.74±3.43 mg/day) with p<0.001. The T1 group had higher hemoglobin (Hb) levels (11.44±2.01 g/dL) than the C (11.04±1.92 g/dL) and T2 groups (10.89±0.67 g/dL) but were not significantly different. In conclusion, regular consumption of jelly-containing SSF increased the daily intake of energy, carbohydrates, fibers, Fe, and Hb levels in adolescent girls with anemia.